Polydopamine coating on additive manufacturing‐based poly lactic acid structures with controllable parameters for enhanced mechanical properties: An experimental investigation. Issue 11 (9th September 2022) - Sharma, Shrutika; Mudgal, Deepa; Gupta, Vishal
Abstract: Dopamine mainly consists of catechol and amine groups in high concentrations that are mainly responsible for interfacial adhesion of dopamine with the substrate and possesses the ability of oxidation through self‐polymerization that results in the formation of polydopamine. The weak mechanical properties of poly lactic acid (PLA) limit its applications in a variety of applications. Polydopamine is widely known for its deposition on a variety of organic and inorganic surfaces. The present study is aimed at studying the effect of the polydopamine coating on mechanical properties of PLA structures fabricated at varying infill density and coated at different concentrations of coating solution immersed for 4 and 7 h. The deposition of polydopamine coating on various PLA structures was confirmed with the help of scanning electron microscopy/energy dispersive spectroscopy analysis. Significant improvement in tensile and compression strengths was found, which was in agreement with the change in weight percentage analysis. The application of polydopamine coating led to improvement in hydrophilicity and degree of crystallinity with the increase in surface roughness of the polymer. The findings from this study will help in utilization of polydopamine‐coated PLA as an alternative over PLA with weak mechanical properties for biomedical applications involving high‐strength biomedical implants and bone tissue engineering. Abstract : Polydopamine Coating on additive manufactured PLA structures